User Preferences in Digital Financial Services: Evidence from Digital Banking Platforms - Nihaya, Ina Uswatun; Kautsar, Achmad; Haryono, Nadia Asandimitra; Kusumawati, Nunik Dwi; Angriani ZN, Sefrimel (Proceeding of International Management Conference and Progressive Papers, 2025)
The rapid growth of digital banking in Indonesia has expanded consumer choice and intensified competition among providers. This study aims to examine user preferences in digital financial services by identifying which digital banks are more frequently chosen by users. Employing a descriptive approach, the study maps patterns of digital bank selection. Data were collected through a survey of 400 respondents in East Java, a province with relatively high adoption of digital financial services. The data were processed and analyzed using SPSS with descriptive statistics (frequency and percentage distributions). The findings indicate that SeaBank emerged as the primary choice, followed by Bank Jago and BLU by BCA Digital, while Allo Bank, Jenius, and Bank Neo Commerce appeared in the next preference group. These results suggest that, despite the increasing number of digital banking alternatives, users tend to focus on certain banks that align more closely with their usage patterns and expectations. This study contributes to the digital finance literature in an emerging-economy context by providing descriptive evidence on digital bank preference patterns. From a practical perspective, the findings offer insights for digital banking providers and relevant stakeholders to better understand user selection tendencies and the competitive landscape of digital banking services. The results may also support broader efforts to strengthen digital financial services and promote financial inclusion in Indonesia.